Evaluation of fodder biomass yield of hydroponically-grown barley and oats and the effects on intake, digestibility and weight gain of Washera sheep when fed as a supplement to a basal diet of natural pasture hay in Ethiopia - Endalew Mekonnen; Yeshambel Mekuriaw; Firew Tegegne; Bimrew Asmare (Tropical Grasslands-Forrajes Tropicales, 2019)
The feasibility of using hydroponically-grown (HGF) barley and oats forage as a supplement to natural pasture hay (PH) for sheep-feeding was investigated. Twenty-five intact Washera male lambs were used in both a 90 day feeding trial and a 10 day digestibility study. The treatments compared were: 100% PH (control, = T1); PH + a concentrate mix (CM) (= T2); PH + HGF barley (= T3); PH + HGF oats (= T4); and PH + 50% CM and 50% HGF mixture of barley and oats (= T5). Chemical composition of diets and refusals, feed intake and digestibility of DM and nutrients were recorded. The average HGF fresh biomass yields from 1 kg grain were 5.21 and 6.32 kg for barley and oats, respectively. The CP, NDF, ADF and ADL concentrations in HGF were 13.2, 45.6, 34.8 and 6.7% for barley and 13.7, 46.8, 36.6 and 7.6% for oats. All supplemented treatments had higher total DM intakes (12‒21%) than the control (P<0.05) and all supplements produced marked substitution effects for PH (35‒51%). Animals on the PH diet lost weight (17 g/d), while all supplemented groups gained weight (58‒65 g/d). Partial budget analysis showed that the highest net return was for T5 followed by T2, T4 and T3. Hydroponically-grown oats forage could have potential to replace a commercial concentrate for supplementing sheep on native pastures, but both HGF and concentrates are probably unaffordable for the majority of smallholder farmers engaged in sheep production. Establishment of farmer cooperative hydroponic facilities could spread the overhead costs of the capital infrastructure and this approach should be investigated.